Effects of Grazing on Above- vs. Below-Ground Biomass Allocation of Alpine Grasslands on the Northern Tibetan Plateau - Zeng, Chaoxu; Wu, Jianshuang; Zhang, Xianzhou (PloS one, 2015)
Biomass allocation is an essential concept for understanding above- vs. below-ground functions and for predicting the dynamics of community structure and ecosystem service under ongoing climate change. There is rare available knowledge of grazing effects on biomass allocation in multiple zonal alpine grassland types along climatic gradients across the Northern Tibetan Plateau. We collected the peak above- and below-ground biomass (AGB and BGB) values at 106 pairs of well-matched grazed vs. fenced sites during summers of 2010-2013, of which 33 pairs were subject to meadow, 52 to steppe and 21 to desert-steppe. The aboveground net primary productivity (ANPP) was represented by the peak AGB while the belowground net primary productivity (BNPP) was estimated from ANPP, the ratio of living vs. dead BGB, and the root turnover rate. Two-ways analyses of variance (ANOVA) and paired samples comparisons with t-test were applied to examine the effects of pasture managements (PMS, i.e., grazed vs. fenced) and zonal grassland types on both ANPP and BNPP. Allometric and isometric allocation hypotheses were also tested between logarithmically transformed ANPP and BNPP using standardized major axis (SMA) analyses across grazed, fenced and overall sites. In our study, a high community-dependency was observed to support the allometric biomass allocation hypothesis, in association with decreased ANPP and a decreasing-to-increasing BNPP proportions with increasing aridity across the Northern Tibetan Plateau. Grazing vs. fencing seemed to have a trivial effect on ANPP compared to the overwhelming influence of different zonal grassland types. Vegetation links above- and below-ground ecological functions through integrated meta-population adaptive strategies to the increasing severity of habitat conditions. Therefore, more detailed studies on functional diversity are essentially to achieve conservation and sustainability goals under ongoing climatic warming and intensifying human influences.